Diffuse pediatric high-grade glioma of methylation-based RTK2A and RTK2B subclasses present distinct radiological and histomolecular features including Gliomatosis cerebri phenotype - Tauziède-Espariat, Arnault; Friker, Lea L.; Nussbaumer, Gunther; Bison, Brigitte; Dangouloff-Ros, Volodia; Métais, Alice; Sumerauer, David; Zamecnik, Josef; Benesch, Martin; Perwein, Thomas; van Vuurden, Dannis; Wesseling, Pieter; et al. (Acta Neuropathologica Communications, 2024)
Diffuse pediatric-type high-grade gliomas (pedHGG), H3- and IDH-wildtype, encompass three main DNA-methylation-based subtypes: pedHGG-MYCN, pedHGG-RTK1A/B/C, and pedHGG-RTK2A/B. Since their first description in 2017 tumors of pedHGG-RTK2A/B have not been comprehensively characterized and clinical correlates remain elusive. In a recent series of pedHGG with a Gliomatosis cerebri (GC) growth pattern, an increased incidence of pedHGG-RTK2A/B (n = 18) was observed. We added 14 epigenetically defined pedHGG-RTK2A/B tumors to this GC series and provided centrally reviewed radiological, histological, and molecular characterization. The final cohort of 32 pedHGG-RTK2A/B tumors consisted of 25 pedHGG-RTK2A (78%) and seven pedHGG-RTK2B (22%) cases. The median age was 11.6 years (range, 4-17) with a median overall survival of 16.0 months (range 10.9-28.2). Seven of 11 of the newly added cases with imaging available showed a GC phenotype at diagnosis or follow-up. PedHGG-RTK2B tumors exhibited frequent bithalamic involvement (6/7, 86%). Central neuropathology review confirmed a diffuse glial neoplasm in all tumors with prominent angiocentric features in both subclasses. Most tumors (24/27 with available data, 89%) diffusely expressed EGFR with focal angiocentric enhancement. PedHGG-RTK2A tumors lacked OLIG2 expression, whereas 43% (3/7) of pedHGG-RTK2B expressed this glial transcription factor. ATRX loss occurred in 3/6 pedHGG-RTK2B samples with available data (50%). DNA sequencing (pedHGG-RTK2A: n = 18, pedHGG-RTK2B: n = 5) found EGFR alterations (15/23, 65%; predominantly point mutations) in both subclasses. Mutations in BCOR (14/18, 78%), SETD2 (7/18, 39%), and the hTERT promoter (7/19, 37%) occurred exclusively in pedHGG-RTK2A tumors, while pedHGG-RTK2B tumors were enriched for TP53 alterations (4/5, 80%). In conclusion, pedHGG-RTK2A/B tumors are characterized by highly diffuse-infiltrating growth patterns and specific radiological and histo-molecular features. By comprehensively characterizing methylation-based tumors, the chance to develop specific and effective therapy concepts for these detrimental tumors increases.